Waterproof cone of loudspeaker and preparation method thereof
By using mixed pulp of sulfite pulp and micro-nano pulp, the speaker paper cone is obtained directly through papermaking and hot pressing molding, solving the problems of complex and harmful substances of existing methods, achieving high waterproofing and hardness, reducing costs and improving sound quality.
Patent Information
- Application Number
- CN202411783559.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
AI Technical Summary
The existing speaker paper cone preparation method is complex and costly, and the materials used contain harmful substances, making it difficult to meet the requirements of waterproofing and hardness.
A mixed pulp of sulfite pulp and micro-nano pulp is used to directly obtain the waterproof paper basin body through papermaking and hot pressing, eliminating the impregnation and hardening and waterproofing treatment processes.
It achieves high waterproof performance and hardness of paper cones, reaches IP67-level waterproofing level, reduces costs, and does not contain harmful substances, and improves the purity of sound quality.
Smart Images

Figure CN119653300A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a waterproof paper cone of a loudspeaker and a preparation method thereof. Background Art
[0002] The paper cones of loudspeakers, especially those for outdoor use (such as pedestrian warning devices), are mostly required to have good waterproof effects to prevent the paper cones from being deformed by water and to prevent water vapor from entering the interior of the loudspeaker, causing damage to the voice coil, magnetic circuit and other internal components of the loudspeaker, or affecting the sound performance of the loudspeaker.
[0003] The conventional method for preparing waterproof paper cones for speakers includes: the pulp is sent to a beating machine for beating, and after a period of time, it is sent to a paper cone forming machine for papermaking, the cylinder is evacuated to extract the water in the pulp, and the pulp is formed into a paper cone on a dewatering mold, and then the cone cone is hot-pressed, impregnated and hardened, and waterproofed to make the cone meet the hardness and waterproof performance requirements, such as a layer of waterproof resin attached to the surface; finally, the cone of the cone is cut off. The existing paper cone preparation method requires impregnation and hardening, waterproofing process treatment, etc. after the paper cone is papermade and hot-pressed. The process is complicated and the cost is high. In addition, the materials used in the impregnating agent, waterproof glue, etc. mostly use organic solvents and contain certain harmful substances.
[0004] The above information disclosed in the Background section is only for enhancement of understanding of the background of the present application and therefore it may contain information that does not constitute the prior art that is already known to a person of ordinary skill in the art. Summary of the invention
[0005] In view of this, the present invention provides a waterproof paper cone of a speaker and a preparation method thereof, which does not require additional waterproofing steps and impregnation and hardening steps. The formed paper cone itself has good waterproof performance and hardness and does not contain harmful substances.
[0006] The first aspect of the present invention adopts the following technical solution:
[0007] A method for preparing a waterproof paper cone of a speaker comprises the following steps:
[0008] (1) mixing sulfite pulp and micro-nano pulp into mixed pulp, wherein the weight percentage of the micro-nano pulp in the mixed pulp is 3-20%, and the micro-nano pulp contains 5-25% by weight of micro-nano paper fibers, wherein the average length of the micro-nano paper fibers is 1-10 mm, and the average width is 0.1-100 μm;
[0009] (2) adding an auxiliary agent to the mixed pulp, using a dewatering die of a papermaking machine to make paper, and removing water from the pulp on the dewatering die by vacuuming to form a paper cone blank;
[0010] (3) separating the paper cone blank from the dehydration mold and hot pressing the paper cone blank;
[0011] (4) Cutting to obtain the finished paper cone body.
[0012] In a preferred embodiment, the preparation method further comprises step (5): connecting an elastic edge to the outer edge of the finished paper cone body to obtain a finished paper cone. The elastic edge is also called a folding ring and is used to suspend the paper cone body on a speaker bracket (basin bracket). In a specific embodiment, the elastic edge is a rubber edge, which is elastic and allows the paper cone to vibrate and emit sound after being connected to the speaker bracket.
[0013] In a preferred embodiment, the micro-nano pulp contains 8-15% micro-nano paper fibers, the average length of the micro-nano paper fibers is 1-3 mm, the average width is 10-50 μm. Furthermore, the average length of the micro-nano paper fibers is 1-2.5 mm, and the average width is 30-50 μm.
[0014] In a preferred embodiment, the Zeta potential of the micro-nano paper fiber is -60 to -10 mV. In a more preferred embodiment, the Zeta potential of the micro-nano paper fiber is -50 to -40 mV.
[0015] In a preferred embodiment, the pH of the micro-nano pulp is 12 to 14. More preferably, the pH of the micro-nano pulp is 12 to 13; further, 12 to 12.5.
[0016] In a preferred embodiment, in step (2), the dehydration mold has a conical or truncated cone upper surface; in step (4), the cut paper cone body is a truncated cone-shaped paper cone.
[0017] In a preferred embodiment, in step (2), the auxiliary agent includes a combination of one or more selected from a waterproofing agent, a hardener and an acidity regulator. The waterproofing agent may include ODG; the hardener may include P615; and the acidity regulator may include AL2(SO4)3.
[0018] In a preferred embodiment, the weight ratio of the auxiliary agent to the mixed pulp is 0.05 to 0.15. More preferably, the weight ratio of the auxiliary agent to the mixed pulp is 0.08 to 0.1.
[0019] In a preferred embodiment, in step (1), sulfite pulp and micro-nano pulp are obtained by beating with a beating machine, the beating time is 3 to 10 hours, and the beating degree is 20°SR to 80°SR. In a specific and preferred embodiment, sulfite pulp is prepared by the following steps: first soak the sulfite pulp paperboard in water for 1 to 2 hours, then manually disperse it in the beating machine and let it free for 10 to 30 minutes before cutting, beating for 3 to 10 hours until the beating degree reaches the desired level, then dyeing is started, and the material is unloaded after the color is fixed. In a specific and preferred embodiment, the micro-nano pulp is prepared by the following steps: mixing the pulp according to a certain proportion, putting it into a beating machine for dispersion for 10 to 300 minutes, wherein the pulp includes one or more of bleached or unbleached coniferous pulp, broadleaf pulp, bamboo pulp, bagasse pulp, cotton pulp, hemp pulp, and waste paper pulp; dehydrating the dispersed pulp to a dryness of 50% to 90%, adding an alkali-alcohol solution with a mass concentration of 5% to 30%, wherein the alkali-alcohol solution is a combination of one or more of sodium methoxide, sodium ethoxide, potassium ethoxide, ethanolamine, sodium tert-butoxide, quaternary ammonium alkali, potassium hydroxide, and sodium hydroxide, and the solvent is one or more of methanol, ethanol, or isopropanol. combination; then adding a surfactant in an amount of 0 to 0.6% by mass ratio to the absolute dry pulp, wherein the surfactant is a combination of one or more of fatty alcohol polyoxyethylene ether, alkyl glycoside, and alkyl sulfonate; then adding a halide in an amount of 1:0.5 to 5 by mass ratio to the absolute dry pulp, wherein the halide is a combination of one or more of 3-chloro-2-hydroxypropyltrimethylammonium chloride, sodium 3-chloro-2-hydroxypropanesulfonate, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid or sodium chloroacetate; heating the mixed dispersion to 40 to 120° C., stirring for 10 to 120 min at a stirring speed of 200 to 2400 rpm, and obtaining a reacted micro-nano slurry with a concentration of 0.1% to 20%.
[0020] In a preferred embodiment, in step (2), the vacuum degree of the vacuum pumping is -30 to 40 KPa.
[0021] In a preferred embodiment, in step (3), the pressure of hot pressing is 2-10 Kgf / cm 2 The hot pressing time is 8 to 20 seconds, and the hot pressing temperature is 150 to 250°C.
[0022] Another aspect of the present invention adopts the following technical solution:
[0023] A speaker paper cone is manufactured according to the manufacturing method.
[0024] In a preferred embodiment, the speaker cone is a woofer cone. The cone includes a truncated cone-shaped cone, which is directly obtained from steps (1) to (4) in the above preparation method. The cone meets the hardness and waterproof requirements, and the waterproof grade can meet the requirements of IP67, and no impregnation hardening process and waterproof treatment process are required.
[0025] The present invention adopts the above scheme and has the following advantages:
[0026] The preparation method of the speaker paper cone of the present invention adopts mixed paper pulp containing 3-20% by weight of micro-nano paper pulp, wherein the micro-nano paper pulp contains micro-nano paper fibers, and the main body of the finished paper cone is directly obtained by cutting after papermaking and hot pressing, and no impregnation and hardening process and waterproofing process are required. The main body of the obtained finished paper cone can directly meet the requirements of hardness and waterproofing, wherein the waterproofing level can reach IP67 level, which is conducive to reducing the cost of the paper cone, and the main body of the paper cone does not contain harmful substances such as organic solvents. The speaker using the paper cone can obtain a relatively smooth frequency response curve, with low distortion and relatively clean sound quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0028] Figure 1 and 2 These are microscope photographs of different magnifications of a micro-nano paper fiber used in an embodiment of the present invention.
[0029] Figure 3 This is a length distribution diagram of micro-nano paper fibers used in an embodiment of the present invention.
[0030] Figure 4 A width distribution diagram of a micro-nano fiber used in an embodiment of the present invention.
[0031] Figure 5 A joint distribution diagram of length and width of a micro-nano fiber used in an embodiment of the present invention.
[0032] Figure 6 The following are photos of the paper basin bodies prepared in the examples and comparative examples before and after the waterproof test.
[0033] Fig. 7A and Figure 7B The nanoindentation test results of Example 2 and the comparative example are shown.
[0034] Figure 8 The figure is a structural diagram of a woofer according to an embodiment of the present invention.
[0035] Fig. 9 for Figure 8 The frequency response curve of the subwoofer is shown.
[0036] Fig.10 for Figure 8 Distortion graph of the subwoofer shown. DETAILED DESCRIPTION
[0037] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0038] In this document, the directions or positional relationships indicated by the terms "upper", "lower", "front", "rear", etc. are based on the directions or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present application and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present application.
[0039] A method for preparing a waterproof paper cone of a speaker comprises the following steps:
[0040] (1) mixing sulfite pulp and micro-nano pulp to form a mixed pulp, wherein the mass percentage of sulfite pulp in the mixed pulp is 80-97%, the weight percentage of the micro-nano pulp is 3-20%, the micro-nano pulp contains 5-25% by weight of micro-nano paper fibers, and the average length of the micro-nano paper fibers is 1-10 mm and the average width is 0.1-100 μm;
[0041] (2) adding an auxiliary agent to the mixed pulp, using a dewatering die of a papermaking machine to make paper, and removing water from the pulp on the dewatering die by vacuuming to form a paper cone blank;
[0042] (3) separating the paper cone blank from the dehydration mold and hot pressing the paper cone blank;
[0043] (4) Cutting to obtain the finished paper cone body;
[0044] (5) An elastic edge is connected to the outer edge of the finished paper cone body to obtain a finished paper cone.
[0045] In step (1), the micro-nano pulp contains 8-15% micro-nano paper fibers, the average length of the micro-nano paper fibers is 1-3 mm, and the average width is 10-50 μm. Further, the average length of the micro-nano paper fibers is 1-2.5 mm, and the average width is 30-50 μm. The Zeta potential of the micro-nano paper fibers is -60 to -10 mV; more preferably, the Zeta potential of the micro-nano paper fibers is -50 to -40 mV. The pH of the micro-nano pulp is 12 to 14; more preferably, the pH of the micro-nano pulp is 12 to 13; further 12 to 12.5.
[0046] In step (1), sulfite pulp and micro-nano pulp are obtained by beating with a beating machine, the beating time is 3 to 10 hours, and the beating degree is 20°SR to 80°SR. In a specific and preferred embodiment, sulfite pulp is prepared by the following steps: first, sulfite pulp paperboard is soaked in water for 1 to 2 hours, then manually dispersed into a beating machine and allowed to free for 10 to 30 minutes before cutting, beating for 3 to 10 hours until the beating degree reaches a certain level, then dyeing is started, and the material is cut after the color is fixed.
[0047] The micro-nano pulp is prepared by the following steps: mixing pulp according to a certain proportion, putting it into a beating machine for dispersion for 10 to 300 minutes, wherein the pulp comprises one or more of bleached or unbleached coniferous wood pulp, broadleaf wood pulp, bamboo pulp, bagasse pulp, cotton pulp, hemp pulp, and waste paper pulp; dehydrating the dispersed pulp to a dryness of 50% to 90%, adding an alkali alcohol solution with a mass concentration of 5% to 30%, wherein the alkali alcohol solution is a combination of one or more of sodium methoxide, sodium ethoxide, potassium ethoxide, ethanolamine, sodium tert-butoxide, quaternary ammonium alkali, potassium hydroxide, and sodium hydroxide, and the solvent is a combination of one or more of methanol, ethanol, or isopropanol; and then adding an absolute A surfactant is added at a dry pulp mass ratio of 0 to 0.6%, wherein the surfactant is a combination of one or more of fatty alcohol polyoxyethylene ether, alkyl glycoside, and alkyl sulfonate; a halide is added at a mass ratio of 1:0.5 to 5 to the absolute dry pulp, wherein the halide is a combination of one or more of 3-chloro-2-hydroxypropyltrimethylammonium chloride, sodium 3-chloro-2-hydroxypropanesulfonate, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid or sodium chloroacetate; the mixed dispersion is heated to 40 to 120° C., stirred for 10 to 120 minutes at a stirring speed of 200 to 2400 rpm, to obtain a reacted micro-nano slurry with a concentration of 0.1% to 20%.
[0048] In step (2), the dewatering mold has a conical or truncated conical upper surface. The auxiliary agent includes a combination of one or more selected from a waterproofing agent, a hardener and an acidity regulator. Among them, the waterproofing agent may include ODG; the hardener may include P615; the acidity regulator may include AL2(SO4)3. The weight ratio of the auxiliary agent to the mixed pulp is 0.05 to 0.15. More preferably, the weight ratio of the auxiliary agent to the mixed pulp is 0.08 to 0.1.
[0049] In step (2), the vacuum degree of the vacuum pumping is -30 to 40 KPa.
[0050] In step (3), the pressure of hot pressing is 2-10 Kgf / cm 2 The hot pressing time is 8 to 20 seconds, and the hot pressing temperature is 150 to 250°C.
[0051] In step (4), the cut paper cone body is a paper cone in the shape of a truncated cone.
[0052] In step (5), the elastic edge is bonded to the outer edge of the paper cone body by glue.
[0053] Examples 1 to 3: Preparation of paper cones
[0054] (1) Preparation of sulfite pulp
[0055] First, soak the sulfite pulp paperboard in water for 2 hours, then manually disperse it into the debonding machine and let it free for 30 minutes before cutting. After debonding for 8 hours, start dyeing after the debonding degree reaches the required level. After the color is fixed, unload the paperboard.
[0056] (2) Preparation of micro-nano pulp
[0057] A pretreatment liquid was added to bleached coniferous pulp (1000 g, calculated as absolute dry pulp, the same below) with a beating degree of 60°SR, wherein the pretreatment liquid contained 0 parts of fatty alcohol polyoxyethylene ether, 15 parts of 3-chloro-2-hydroxypropyltrimethylammonium chloride, and 85 parts of isopropanol, and the mass ratio of absolute dry pulp to 3-chloro-2-hydroxypropyltrimethylammonium chloride was 1:1.5. The pulp was stirred at a high speed of 1500 r / min for 5 minutes to obtain a pretreated pulp with a concentration of 9%; a sodium hydroxide / isopropanol solution with a mass concentration of 20% was added to the pretreated pulp, and the mass ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to sodium hydroxide was controlled to be 1:1.2. The pulp was heated to 80°C and stirred for 30 minutes at a stirring speed of 1500 r / min to obtain a micro-nano pulp with a concentration of 5%.
[0058] Among them, the microscope photos of micro-nano pulp are as follows: Figure 1 and Figure 2 As shown, Figures 3 to 5 The length and width distribution of the micro-nano paper fibers are shown. Specifically, the micro-nano paper fibers in the micro-nano pulp have a solid content of 9.35%; pH: 12.15; average length: 1.782 mm; average width: 37.9 μm; and Zeta potential: -49.5 mV. The specific parameters of the micro-nano paper pulp are shown in Table 1 below.
[0059] Table 1
[0060]
[0061]
[0062] (3) Preparation of mixed pulp
[0063] According to the ratio in Table 2 below, the conventional sulfite pulp obtained in step (1) is added to the material tank, and the self-made micro-nano pulp obtained in step (2) is added to the same material tank, a little water is added and stirred evenly, and then a total of 10 wt.% of waterproofing agent, hardener and acidity regulator are added in sequence, stirred for 5 to 10 minutes, and then water is added to the required position.
[0064] (4) Molding
[0065] The paper is made using a dewatering mold of a paper machine, and water in the pulp on the dewatering mold is removed by vacuuming to form a paper cone blank. The paper cone blank is separated from the dewatering mold and hot-pressed. The main body of the finished paper cone is obtained by cutting with a punching machine. The upper surface of the dewatering mold is conical or truncated conical, so that the pulp layer formed by drawing paper is conical or truncated conical.
[0066] (5) Elastic edge
[0067] The finished paper cone is manufactured by connecting an elastic edge to the outer edge of the finished paper cone body.
[0068] Comparative example: 100% sulfite pulp paper cone
[0069] The conventional sulfite pulp prepared in step (1) of Examples 1 to 3 is added to a material tank, a little water is added and stirred evenly, and then a total of 10 wt.% of a waterproofing agent, a hardener and an acidity regulator are added in sequence and stirred for 5 to 10 minutes before adding water to the required position. The paper is made using a dewatering die of a paper machine, and the water in the pulp on the dewatering die is removed by vacuum to form a paper cone blank. The paper cone blank is separated from the dewatering die, and the paper cone blank is hot-pressed to directly obtain the main body of the finished paper cone without the impregnation hardening and waterproofing treatment steps.
[0070] Test evaluation of Examples 1 to 3 and comparative examples
[0071] Waterproof test method: add water to the front of the paper basin that has not been punched in the middle, so that the front of the paper basin contacts the water. After leaving it for 24 hours, pour out the remaining water on the front of the paper basin and visually observe whether the front is soaked by water and whether the back is leaking. The test results are shown in Table 2 and Figure 6 .in, Figure 6 Part A (upper side) in the middle shows the front and back of the paper basin of Example 1 after the waterproof test. The front is basically not soaked, and there is no water seepage on the back; Figure 6 Part B (middle) shows the front side of the paper cone of Example 2 after the waterproof test. The front side is not soaked, and the residual water in the upper part adheres to the surface in the form of water droplets, which can be easily removed; Figure 6 Part C in the middle shows the front sides of two paper cone samples of the comparative example after the waterproof test. Although there is no water seepage on the back side, a large area of the front side of the paper cone is soaked, and the waterproof effect is poor.
[0072] Hardness test method: The hardness of the paper cone was determined by nanoindentation measurement using an NMT-04 nanomechanical testing system (FemtoTools, Buchs, Switzerland) equipped with a Berkovich diamond tip. The specific test method is to load the force from 0 to 200μN, 400μN, and 800μN at a constant loading speed of 40μN / s, and then unload after holding the pressure for 10s. The corresponding hardness data was fitted according to the test curve. Fig. 7A and Figure 7B The nanoindentation test result diagrams of Example 2 and the comparative example are shown respectively.
[0073] The pulp composition and performance test data of Examples 1 to 3 and the comparative example are shown in Table 2 below.
[0074] Table 2
[0075]
[0076] Example 4: Subwoofer
[0077] This embodiment provides a bass speaker. Figure 8 As shown, the woofer 100 mainly includes a paper cone 1, a bracket 2, a voice coil 3, a dust cap 4, a magnetic circuit 5 and a damper 6. The paper cone 1 is the paper cone prepared in Example 2. The paper cone 1 includes a main body 11 and an elastic edge 12 arranged around the main body 11. The main body 11 is suspended on the bracket 2 by the elastic edge 12. The main body 1 is directly obtained by steps (1) to (4) in the above-mentioned preparation method; the elastic edge 12 is a rubber elastic edge, and the elastic edge 12 has an arc-shaped portion with the middle portion arched upward. The main body 11 is in the shape of a truncated cone as a whole, and a hollow is opened at the top of the cone.
[0078] The elastic edge 12 of the paper cone 1 is glued to the bracket 2. A central hole is opened in the middle of the main body 11 of the paper cone 1, and the voice coil 3 passes through the central hole and fits tightly. Driven by the voice coil 3, the paper cone 1 vibrates to form sound waves. The dust cap 4 is used to cover the central hole of the paper cone 1 or the upper end of the voice coil 3 to prevent water vapor, dust, etc. from entering the interior of the voice coil 3 and the magnetic circuit 5. The dust cap 4 is fixed to the upper end of the voice coil 3, so that the upper end of the voice coil 3 is closed. The magnetic circuit 5 includes magnetic steel and magnetic conductive components to form a magnetic field; there is a magnetic gap 51 inside the magnetic circuit 5, and the lower end (coil part) of the voice coil 3 is inserted into the magnetic gap 51. After the coil of the voice coil 3 is connected to the electroacoustic signal, it cuts the magnetic flux line under the action of the magnetic field, so that it can reciprocate along its center line, thereby driving the paper cone 1 to vibrate and make sound. Furthermore, the middle of the bracket 2 has a horizontal step portion, the outer edge of the elastic wave 6 is fixed on the step portion, and the inner edge is sleeved on the voice coil 3 and tightly matched with the voice coil 3 to prevent the voice coil 3 from shaking in a direction other than the expected direction (i.e., the expected vibration direction of the paper cone 1). The upper end of the magnetic circuit 5 is fixed to the bottom of the bracket 2, for example, the two are glued to each other. The bracket 2 is provided with a plurality of sound-transmitting holes 21 along the circumferential direction to connect the inner cavity on the back of the paper cone 1 with the outside.
[0079] The sound reproduction performance of the above-mentioned subwoofer was tested, and the frequency curve is shown in Fig. 9 As shown, the distortion curve is Fig.10 See Fig. 9 The frequency response curve of the bass speaker of this embodiment is relatively smooth, especially in the frequency range of 80 to 1100 Hz, the sound reproduction effect is better. Fig.10 The total distortion (THD) of the woofer speaker of this embodiment in the frequency band of 60 Hz to 10 KHz is less than 2%, and the overall distortion is relatively small.
[0080] As shown in this specification and claims, the terms "comprises" and "include" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list, and the method or device may also include other steps or elements. The term "and / or" as used herein includes any combination of one or more of the relevant listed items.
[0081] It is further understood that in the present disclosure, "plurality" refers to two or more than two, and other quantifiers are similar thereto.
[0082] It should be noted that, unless otherwise specified, when a feature is referred to as being “fixed” or “connected” to another feature, it may be directly fixed or connected to the other feature, or it may be indirectly fixed or connected to the other feature.
[0083] The above embodiment is only for illustrating the technical concept and features of the present invention, and is a preferred embodiment. Its purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a waterproof paper cone of a speaker, characterized in that: The steps include: (1) mixing sulfite pulp and micro-nano pulp into mixed pulp, wherein the weight percentage of the micro-nano pulp in the mixed pulp is 3-20%, and the micro-nano pulp contains 5-25% by weight of micro-nano paper fibers, wherein the average length of the micro-nano paper fibers is 1-10 mm, and the average width is 0.1-100 μm; (2) adding an auxiliary agent to the mixed pulp, using a dewatering die of a papermaking machine to make paper, and removing water from the pulp on the dewatering die by vacuuming to form a paper cone blank; (3) separating the paper cone blank from the dehydration mold and hot pressing the paper cone blank; (4) Cutting to obtain the finished paper cone body.
2. The preparation method according to claim 1, characterized in that: The preparation method further comprises step (5): connecting an elastic edge to the outer edge of the finished paper cone body to obtain a finished paper cone.
3. The preparation method according to claim 1, characterized in that: The micro-nano pulp contains 8-15% of micro-nano paper fibers. The average length of the micro-nano paper fibers is 1-3 mm, and the average width is 10-50 μm.
4. The preparation method according to claim 1 or 3, characterized in that: The Zeta potential of the micro-nano paper fiber is -60 to -10 mV.
5. The preparation method according to claim 4, characterized in that: The Zeta potential of the micro-nano paper fiber is -50 to -40 mV.
6. The preparation method according to claim 1, characterized in that: The pH of the micro-nano pulp is 12-14.
7. The preparation method according to claim 1, characterized in that: In step (2), the dehydration mold has an upper surface that is conical or truncated conical; in step (4), the cut paper cone body is a paper cone in the shape of a truncated cone.
8. The preparation method according to claim 1, characterized in that: In step (2), the auxiliary agent includes a combination of one or more selected from the group consisting of a waterproofing agent, a hardener and an acidity regulator; and the weight ratio of the auxiliary agent to the mixed pulp is 0.05 to 0.
15.
9. The preparation method according to claim 1, characterized in that: In step (1), sulfite pulp and micro-nano pulp are obtained by beating with a beating machine, the beating time is 3 to 10 hours, and the beating degree is 20°SR to 80°SR; in step (2), the vacuum degree of vacuuming is -30 to 40 KPa; in step (3), the pressure of hot pressing is 2 to 10 Kgf / cm 2 The hot pressing time is 8 to 20 seconds, and the hot pressing temperature is 150 to 250°C.
10. A speaker cone, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 9.